2021
DOI: 10.1159/000516015
|View full text |Cite
|
Sign up to set email alerts
|

The State of Peptide Receptor Radionuclide Therapy and Its Sequencing among Current Therapeutic Options for Gastroenteropancreatic Neuroendocrine Tumors

Abstract: Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) are the most common form of neuroendocrine neoplasia, but there is no current consensus for the sequencing of approved therapies, particularly with respect to peptide receptor radionuclide therapy (PRRT). This comprehensive review evaluates the data supporting approved therapies for GEP-NETs and recommendations for therapeutic sequencing with a focus on how PRRT currently fits within sequencing algorithms. The current recommendations for PRRT sequencing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
3
0
2
Order By: Relevance
“…Therefore, the pooled data from our systematic review show that tumor debulking plays a key role in controlling paraneoplastic hypercalcemia in patients with well-differentiated NEN, so surgical treatment should be indicated whenever feasible. PRRT was administered in a limited number of cases; however, given its capability to control functioning tumors [ 105 ] and its potential role as a neoadjuvant therapy [ 106 , 107 , 108 ], PRRT could be prescribed either before surgery or in patients with progressive metastatic inoperable disease to reduce tumor secretion and tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pooled data from our systematic review show that tumor debulking plays a key role in controlling paraneoplastic hypercalcemia in patients with well-differentiated NEN, so surgical treatment should be indicated whenever feasible. PRRT was administered in a limited number of cases; however, given its capability to control functioning tumors [ 105 ] and its potential role as a neoadjuvant therapy [ 106 , 107 , 108 ], PRRT could be prescribed either before surgery or in patients with progressive metastatic inoperable disease to reduce tumor secretion and tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…There is no current consensus on the sequencing of approved therapies, particularly with respect to PRRT. Available evidence is mostly derived from retrospective and, therefore, potentially biased series [ 8 , 74 , 185 ]. A recent retrospective multicenter Italian study showed that [ 177 Lu]Lu-DOTA-TATE, as well as non-conventional-dose somatostatin analogues [ 186 ], are better tolerated than chemotherapy or everolimus, with no significant difference in PFS [ 187 ].…”
Section: Somatostatin Analogues For Targeted Therapymentioning
confidence: 99%
“…There are no robust categorized levels of evidence on optimal treatment strategies (i.e., order of administration, number of cycles, efficacy of combinations, and switching criteria) for scenarios often encountered in clinical practice. Currently available clinical data on treatment sequencing are restricted to a small number of retrospective studies [ 45 ].…”
Section: Translating Clinical Research Into Therapeutic Strategymentioning
confidence: 99%